Método de avaliação do espaço urbano quanto à seguridade percebida pelas mulheres ao caminharem - Rodrigues, Lara Reis (2024)
Walking is the most basic and fundamental way of mobility, allowing connectivity and interaction between the individual and the built environment. However, research has demonstrated that the characteristics of the built environment influences the perceived security by pedestrians and the option to walk. Furthermore, gender is one of the most relevant variables in this aspect, considering that the chances of women choosing to travel on foot are approximately twice smaller compared to men. Bearing in mind that security concerns the prevention of risks to the personal, physical and psychological integrity of the individual, this research is based on the following question: what evaluation method can support the planning of urban areas perceptibly more secure for walking, especially for women? Thus, the general objective of this work was to propose a method of evaluating of the urban space in terms of the perceived security by women when walking. The study consisted of three stages: (1) selection of characteristics of the built environment that interfere on the perceived security of pedestrians, considering mainly the female gender; (2) definition of an instrument of evaluating of the perception of security of the pedestrian in urban spaces, through the Analytic Hierarchy Process (AHP); and (3) carrying out a case study in an urban area with the aim of mapping locations that are more or less secure perceptibly for pedestrians, considering gender, using a Geographic Information System (GIS). For the development of the stage 1, a bibliographical review was carried out about the topic, made possible through analysis of national and international publications, of scientific and technical nature, available in libraries and virtual search engines. In the stage 2, a questionnaire was applied to obtain the weights and the prioritization hierarchy of the measures and aspects previously selected, through the perception of the interviewees, considering the general average and the gender filter, as well as ethnicity, age group and sexual orientation. As for the stage 3, the central area of the city of Franca (SP) was delimited as the object of study. In general, the results are (i) the proposal of eight measures grouped into four aspects of the urban space; (ii) obtaining the following prioritization hierarchy, from the most important aspect to the least important by the general average: circulation of people (0,30), surveillance (0,27), street maintenance (0,22) and attractiveness of the urban space (0,21); and (iii) visualization of differences in the evaluation of the study area regarding to the perception of security between female and male pedestrians. The work supports public management with regard to the urban and transport planning, in addition to contributing to the state of the art through the selection, consideration and mapping of the main characteristics of the built environment that affects the perceived security when walking.